Risk Management in Clinical and Biochemical Laboratories During the Covid-19 Pandemic (International Journal of Contemporary Security Studies, 2023)
The COVID-19 pandemic is a major challenge for clinical-biochemical laboratories. Laboratory managers face demands to maintain the productivity and quality of laboratory diagnostics, while protecting laboratory staff from a new pathogen that the medical public has only just begun to reveal. This paper describes the experiences of the Center for Medical Biochemistry of the University Medical Center of Serbia (CMB UCCS) in risk management during the COVID-19 pandemic. During the pandemic, this reference center, the first accredited laboratory in Serbia, provided more than 4.5 million tests in the field of modern laboratory diagnostics for COVID-19 patients. The paper will describe a site- and activity-specific risk assessment of the laboratory to identify and mitigate risks, measures to protect against potential risks from infectious samples, with a focus on staff safety and prevention of biohazard exposure. CMB UCCS risk management strategy based on IFCC, WHO, CLSI M29A4 risk management recommendations will be analyzed. From today’s viewpoint, the main precondition for successful risk management during a pandemic is the timely provision of laboratory facilities, i.e. that laboratories should have enough staff to be flexible in their work, that the staff have adequate protective equipment and resources for work, and that managers are experienced and ready to work effectively in crisis situations, taking into account the implementation of motivation strategies and promoting the mental and physical health of employees.
Keywords: pandemic, medical laboratories, COVID-19, risk management, Serbia